The Use of Language Sample Analysis to Differentiate Developmental Language Disorder From Typical Language in Bilingual Children: A Systematic Review and Meta-Analysis. - Ortiz, José A.; Nolasco, Jessica M.; Yi Ting Huang; Chow, Jason C. (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Language sample analysis (LSA) is a commonly recommended method of assessment for bilingual children. This systematic review and metaanalysis provides a comprehensive overview of the literature on the use of LSA to differentiate between developmental language disorder (DLD) and typical language (TL) in bilingual children. Method: We conducted a search of several large electronic databases along with forward and backward searches and applied abstract and full-text screening procedures to identify all relevant studies. We then estimated standardized mean differences, representing the ability of LSA to differentiate between DLD and TL, using multilevel model and subgroup and moderator analyses to identify characteristics of LSA that may be associated with differences in effect size magnitude. We conducted assessments of publication bias and risk of bias by examining quality indicators for each study. Results: The search yielded 35 articles that met the inclusion criteria. Participants ranged in age from 2;0 (years;months) to 11;9, with over 40 languages represented. Across studies, the pooled standardized mean difference indicated that children with DLD performed 0.78 SD lower on LSA measures than those with TL. Measures of morphosyntactic accuracy exhibited the largest pooled effect size. Elicitation method, language of task, and age were not associated with differences in effect size. Discussion: Results of this study provide evidence of the clinical utility of LSA in differentiating between DLD and TL in bilingual children. Further research is needed to examine classification accuracy as well as task characteristics that may improve its diagnostic utility.